Small Molecule Analysis of Extracellular Vesicles Produced by Cryptococcus gattii: Identification of a Tripeptide Controlling Cryptococcal Infection in an Invertebrate Host Model - Reis, Flavia C. G.; Costa, Jonas H.; Honorato, Leandro; Nimrichter, Leonardo; Fill, Taícia P.; Rodrigues, Marcio L. (Frontiers in Immunology, 2021)
The small molecule (molecular mass < 900 Daltons) composition of extracellular vesicles (EVs) produced by the pathogenic fungus Cryptococcus gattii is unknown, which limits the understanding of the functions of cryptococcal EVs. In this study, we analyzed the composition of small molecules in samples obtained from solid cultures of C. gattii by a combination of chromatographic and spectrometric approaches, and untargeted metabolomics. This analysis revealed previously unknown components of EVs, including small peptides with known biological functions in other models. The peptides found in C. gattii EVs had their chemical structure validated by chemical approaches and comparison with authentic standards, and their functions tested in a Galleria mellonella model of cryptococcal infection. One of the vesicular peptides (isoleucine-proline-isoleucine, Ile-Pro-Ile) improved the survival of G. mellonella lethally infected with C. gattii or C. neoformans. These results indicate that small molecules exported in EVs are biologically active in Cryptococcus. Our study is the first to characterize a fungal EV molecule inducing protection, pointing to an immunological potential of extracellular peptides produced by C. gattii.